Upper Permian, Scythian, and Anisian rocks in the Žiri area - Grad, Karel; Ogorelec, Bojan (Geologija, 1980)
Three continous sections from the Žiri area in Slovenia serve to interpret the sedimentary environments during the time interval between the Upper Permian and Anisian stages. The corresponding rock sequences were investigated by biostratigraphical, sedimentological, and geochemical methods. In general, dolomite of early diagenetic origin prevails, intercalated with cellular variety and evaporites in the lower part of Upper Permian. It is overlain by Bellerophon limestone in some restricted sections. The Scythian carbonate rocks are interbedded with clastic deposits containing well developed lenticular oolitic limestone. The Anisian dolomite, characterized by Meandrospira dinarica, appears to have been deposited in littoral conditions. As to the distribution and abundance of Chemical elements, the iron and manganese contents are three times higher in the dark Upper Permian dolomite and limestone compared to the light grey dolomite that is transitional in the lithostratigraphic position between Upper Permian and Scythian rocks. Likewise, the Sr and Na contents are higher. The correlation with some sections from the adjacent lands indicates that sea advanced over the Middle Permian Val Gardena beds of Continental origin. A Continental shelf extended from Hungary in the east over Central Slovenia to Northern Italy.